Crystal structure of 1-[(Z)-[4-(4-methoxyphenyl)butan-2-ylidene]amino]-3-phenylurea, C18H21N3O2 - Tan, Ming Yueh; Crouse, Karen A.; Ravoof, Thahira Begum S. A.; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C18H21N3O2, triclinic, P¯1 (no. 2), a=8.5155(4) Å, b=10.6415(4) Å, c=19.0732(10) Å, α=80.918(4)°,